Unilateral reexpansion pulmonary edema after tube thoracostomy: A case report (Indian Journal of Case Reports, 2018)
We report a case of unilateral reexpansion pulmonary edema (RPE) in a patient of secondary spontaneous pneumothorax of 2 days